PERSPEKTIF ISLAM DAN BUDAYA PADA TRADISI BARODAK ADAT PERKAWINAN MASYARAKAT SUMBAWA DI ERA GLOBALISASI - Desmawanti, Rosa; Draditaswari, Silka Yuanti; Widia Nita Kasih, Baiq (The Center for Language Development, Mataram State Islamic University., 2024)
This study examines the Barodak tradition in Sumbawa marriage ceremonies within the context of globalization, focusing on both Islamic and local cultural perspectives. Barodak, a tradition of applying natural-based body scrubs to the bride and groom, has become an inseparable part of the identity of the Sumbawa community. This tradition is not merely a cultural ritual but also reflects religious values that align with the philosophy of Islam, encapsulated in the saying,